Prevalence and characteristics of HPV vaccine hesitancy among parents of adolescent females across Saudi Arabia - Sahar Othman; Ranya Ghamri; Wala Alhamadah; Anwaar Alsatty; Dhuha Khesfaty; Ohoud Alghamdi; Ragad Arbaein; Alaa M. Baglagel; Jumana Khayyat; Bushra Almalki (Frontiers in Public Health)
PurposeVaccination against human papillomavirus (HPV) is pivotal in preventing HPV-related diseases, including cervical cancer. However, vaccine hesitancy and their related factors among parents of adolescent females present a significant obstacle to achieving high vaccination rates. HPV vaccine hesitancy among parents of adolescents and their related factors have been studied at the regional level in Saudi Arabia, but national-level data are not available. Therefore, this study aims to assess the prevalence and characteristics of HPV vaccine hesitancy among parents of adolescent females in Saudi Arabia.Materials and methodsThis cross-sectional study was conducted in Saudi Arabia among parents of adolescent females aged 11–17 years between November and December 2022. The participants completed a self-administered online questionnaire containing the validated Vaccine Hesitancy Scale (VHS), which was originally developed in 2015 by the WHO’s Strategic Advisory Group of Experts (SAGE) on immunization. Descriptive statistics, univariate binomial regression, and multivariate binary logistic regression were employed for statistical analysis.ResultsAmong the 667 participants who completed the questionnaire, 34% were hesitant about immunizing their adolescent daughters with the HPV vaccine. A few demographic variables were significantly associated with vaccine hesitancy, including lower household income and living in the southern region. In addition, lack of recommendation by their healthcare provider and inconvenience related to immunization with the vaccine were also associated with higher levels of hesitancy.ConclusionHPV vaccine hesitancy remains high among parents of adolescent females in Saudi Arabia. More effort needs to be directed toward educating parents, especially during doctor’s visits, in order to increase the acceptance and vaccination rates.